Public sector corruption in Malaysia / Nor Syamaliah Ngah and Azlina Mohd Hussain - Ngah, Nor Syamaliah; Mohd Hussain, Azlina (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2023)
The prevalence of public sector corruption in Malaysia in its more visible forms, which include bribery, embezzlement, fraud, cronyism, bid-rigging, money laundering, extortion, and secret commissions, have been widely discussed and debated at one point or another in public discussions and debates on national news and the social media. The Global Corruption Barometer published by Transparency International, which consisted of a survey for Malaysia, between the time frame from July 2019 to June 2020 where two different governments were in power during that period exhibited, inter alia, that 71% Malaysians think that government corruption is an issue for real concern. Among the public institutions surveyed, Parliament (36%), the Police (30%) and Government officials (28%) were ranked the highest for perception of corruption, respectively. The survey also showed that 39% of all respondents strongly believed that corruption is on the rise.